Discover new knowledge and insights with IDNLearn.com's extensive Q&A platform. Ask anything and receive thorough, reliable answers from our community of experienced professionals.

Help pleaseeeee

Thanksss


Help Pleaseeeee Thanksss class=
Help Pleaseeeee Thanksss class=

Sagot :

Answer:

-y² + 9y² + 9y +2 =?

Step-by-step explanation:

I put the like terms in parenthesis!

-y² + (6y² + 3y²) + (5y + 4y) +3 - 1 ↓

This is now the simplified and combied expression friend, I hope this helped you!

-y² + 9y² + 9y +2 =?

Answer:

[tex]8y^{2} +9y+3[/tex]